Informal Funds Transfer Systems : An Analysis of the Informal Hawala System - El Qorchi, Mohammed (Occasional Papers; Occasional Paper ;, 2003)
Since the terrorist attacks of September 11, 2001, there has been increased public interest in informal funds transfer (IFT) systems. This paper examines the informal hawala system, an IFT system found predominantly in the Middle East and South Asia. The paper examines the historical and socioeconomic context within which the hawala has evolved, the operational features that make it susceptible to potential financial abuse, the fiscal and monetary implications for hawala-remitting and hawala-recipient countries, and current regulatory and supervisory responses.